Persepsi Resiko dan Kemungkinan Hazard Psikologis Para Pekerja Pabrik - Rahmi Indah Syahrina Nasution; Susilawati Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
The work environment is known to contain psychosocial threats such as stressors that cause work stress in employees. Even though it seems that office workers do not need a lot of energy to work, they are vulnerable to stressors such as high quantitative and qualitative job demands. Apart from work stress, work stress can be influenced by differences in individual employee characteristics. Risk perception is the way an individual or group views and assesses the risks that may be faced in a particular situation. Psychosocial includes psychological and social aspects where both aspects influence and influence each other. Psychosocial conditions can be changes in a person's life, both psychological and social, which have reciprocal effects and can lead to mental health or mental health disorders. Employee perceptions of psychosocial hazards in the workplace that may be caused by the context and content of the job. This can cause employees to constantly face psychosocial threats that can affect employees' psychological health. Risk perception has a significant impact on risk management.